Thermo-mechanical study of a novel rotating disk volumetric receiver. (15th July 2021) - Rández, X.; Zaversky, F.; Astrain, D.; Garrido-Maneiro, M.A.; Tortuero, S.; Rico, A.; Poza, P.
Highlights: The complete analysis is composed by material characterization and a CFD and FEM model. The fracture analysis ensures the crack stability, which means the structural integrity of the disks. Stress fields in the disks are not high enough to open the cracks. The maximum circumferential tensile stress appears always on the inner surface of the disks. The higher stresses happen when the air outlet temperature is higher. Abstract: This study evaluates the mechanical behaviour of a ceramic disk which makes up an innovative volumetric absorber design. The new receiver design is formed by a group of disks which are rotating inside a cavity, distributing the radiation absorbed in the aperture to the whole cavity. This research studies the stress fields due to thermal gradients and its effect in the crack propagation in the disks. The complete analysis has been carried out in three steps: the mechanical characterization of the material, in order to know its fracture properties, the computational fluid dynamics (CFD) analysis of the disk, in order to know the temperature distribution in the disk and the finite element model (FEM), which uses as inputs the results of the two previous steps and solves the stress fields in the disk and the fracture behaviour. Fracture and crack growing in the disk have been modelled by using a cohesive element, which, from the fracture properties of the material, allows simulating the crack growing in the disk. This investigation, by means of stress fields and crack propagation analysis, demonstrates the mechanical viability of the disks concept.